Generation of Human CD8 T Regulatory Cells by CD40 Ligand–activated Plasmacytoid Dendritic Cells - Gilliet, Michel (The Rockefeller University Press, 2002)
Although CD8 T cell–mediated immunosuppression has been a well-known phenomenon during the last three decades, the nature of primary CD8 T suppressor cells and the mechanism underlying their generation remain enigmatic. We demonstrated that naive CD8 T cells primed with allogeneic CD40 ligand–activated plasmacytoid dendritic cells (DC)2 differentiated into CD8 T cells that displayed poor secondary proliferative and cytolytic responses. By contrast, naive CD8 T cells primed with allogeneic CD40 ligand–activated monocyte-derived DCs (DC1) differentiated into CD8 T cells, which proliferated to secondary stimulation and killed allogeneic target cells. Unlike DC1-primed CD8 T cells that produced large amounts of interferon (IFN)-γ upon restimulation, DC2-primed CD8 T cells produced significant amounts of interleukin (IL)-10, low IFN-γ, and no IL-4, IL-5, nor transforming growth factor (TGF)-β. The addition of anti–IL-10–neutralizing monoclonal antibodies during DC2 and CD8 T cell coculture, completely blocked the generation of IL-10–producing anergic CD8 T cells. IL-10–producing CD8 T cells strongly inhibit the allospecific proliferation of naive CD8 T cells to monocytes, and mature and immature DCs. This inhibition was mediated by IL-10, but not by TGF-β. IL-10–producing CD8 T cells could inhibit the bystander proliferation of naive CD8 T cells, provided that they were restimulated nearby to produce IL-10. IL-10–producing CD8 T cells could not inhibit the proliferation of DC1-preactivated effector T cells. This study demonstrates that IL-10–producing CD8 T cells are regulatory T cells, which provides a cellular basis for the phenomenon of CD8 T cell–mediated immunosuppression and suggests a role for plasmacytoid DC2 in immunological tolerance.